Improvement of harmonics using passive harmonics filter - Ruhaizad, Ishak; N. F., Helmi; M. S., Jadin; Mohd Redzuan, Ahmad; Airul Sharizli, Abdullah; Emhammed, A. (UTeM, 2018)
Power quality problems are continuously increased and received a great attention due to the impacts on both utilities and consumers. The most frequently reported power quality problem is the harmonics. The aim of this project is to enhance the system performance under the load variation effect through desirable filter placement. In this project, two types of passive filter called single tuned and 3rd order C-type are studied. Load flow analysis is performed to calculate the load bus voltage and total harmonic distortion (THD) that determine the effectiveness of filter application. The work was simulated using Electrical Transient Analyzer Program (ETAP) and tested on two test systems namely the 4-bus and IEEE 14-bus. The results of this work show that single tuned filter is more effective in filtering the harmonic compared to the 3rd order C-type. Furthermore, installing the single tuned filter near to the source of harmonics produces a better result.